MORFOLOGI DAN UMUR PERPINDAHAN ALUR SUNGAI OPAK DI DAERAH BERBAH SLEMAN - Santoso Santoso (Pusat Survei Geologi, 2009)
The morphologic condition of the Opak valley at Dadapan Village, Berbah area, indicates that the Opak River has three times shifted. Based on the passing compass land detail measurement, three paleo river valleys, can be recognized which are separated by terrace morphology. The result of carbon dating by using C14 Â method to the organic clay deposits which was taken from Opak valley 1, 2, 3, and existing river, shows the ages are 6950 years BP, 6800 years BP, 6430 years BP, and 6360 years BP. It proves that the tectonic in this area is very active, because during Upper Holosen (â€¹ 10,000 years) the Opak River has three times shifted.Â Keywords: paleo river channel, shifting, tectonic